Hospital admission time and acute myocardial infarction outcomes in elderly patients from Central Asia - A. G. Nikishin; R. D. Kurbanov; M. M. Pirnazarov (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To identify the specifics of acute myocardial infarction (AMI) clinical course and to study the association between clinical outcomes and hospital admission time among elderly patients from Central Asia. Material and methods. In total, 508 AMI patients were divided into the main group (MG), which included 298 men and women aged over 65 years, and the control group (CG; n=210). The analysed parameters included mean time between AMI onset and hospital admission; percentage of patients hospitalised within first 6 hours; percentage of patients administered streptokinase; streptokinase effectiveness; clinical course of AMI; and in-hospital outcomes. Results. Mean hospital admission time was significantly higher in the MG, compared to the CG: 1220±165 vs. 977±88 minutes (p<0,05). Out of 188 MG patients with ST segment elevation, thrombolytic therapy (TLT) was administered to 14,3 %; in the CG (149 patients with ST segment elevation), the respective percentage was 25,5 %. Clinical course of AMI was similar in both groups. However, the MG was characterised by a significantly higher risk of death (9,4 % vs. 2,86 %; F=0,001; OR 3,53, 95 % CI 1,43—8,67), acute heart failure (33,89 % vs. 21,9 %; F=0,001; OR 1,83, 95 % CI 1,22—2,74), or chronic heart failure (41,31 % vs. 24,76 %; F=0,000; OR 2,62, 95 % CI 1,78—3,86). Conclusion. Elderly patients faced a lower chance of myocardial reperfusion, due to later hospital admission and lower TLT effectiveness, and, as a result, had a higher risk of heart failure.